2020
DOI: 10.1136/archdischild-2020-319173
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric emergency department utilisation during Ramadan: a retrospective cross-sectional study

Abstract: ObjectiveTo investigate the impact of Ramadan on patient characteristics, diagnoses and metrics in the paediatric emergency department (PED).DesignRetrospective cross-sectional study.SettingPED of a tertiary care centre in Lebanon.PatientsAll paediatric patients.ExposureRamadan (June 2016 and 2017) versus the months before and after Ramadan (non-Ramadan).Main outcome measuresPatient and illness characteristics and PED metrics including peak patient load; presentation timings; length of stay; and times to order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…7 8 9 10 11 12 13 The salient findings of these and other studies are discussed below. 7 8 9 10 11 12 13 14 15 16 17 18 19 20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 8 9 10 11 12 13 The salient findings of these and other studies are discussed below. 7 8 9 10 11 12 13 14 15 16 17 18 19 20…”
Section: Resultsmentioning
confidence: 99%
“…Also, Halasa found more patients presenting during the night hours than during daytime hours, echoing previous results; however, he found a larger proportion of younger patients presented with respiratory tract infections during Ramadan. 11 Finally, Balhara et al 13 examined patients in the United Arab Emirates (UAE) and Sawaya et al 20 examined patients in Lebanon, they both observed a reduction in pediatric patient group attendance, with Balhara et al noting a decrease in the length of stay in this group of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of Ramadan on emergency services was reported from two studies. [65][66][67] Faruqi et al [65] analyzed the emergency department (ED) patients' flow during Ramadan and compared it to NR days in a retrospective study from Abu Dhabi, UAE. It was conducted at a tertiary hospital (2014)(2015)(2016).…”
Section: Medical Emergenciesmentioning
confidence: 99%
“…Moreover, the authors observed a difference in the patient arrival pattern between the Ramadan and NR days and the predominant categorization of chief patient complaints. Sawaya et al [66] investigated the impact of Ramadan on patient characteristics, diagnoses, and metrics in the pediatric ED (PED). In a retrospective cross-sectional study, all pediatric patients attending the PED of a tertiary care center in Lebanon were included during Ramadan (June 2016 and 2017) versus the months before and after Ramadan (NR).…”
Section: Medical Emergenciesmentioning
confidence: 99%